Detection of glyco‐mucin profiles improves specificity of MUC16 and MUC1 biomarkers in ovarian serous tumours. Issue 2 (22nd October 2014) - Ricardo, Sara; Marcos-Silva, Lara; Pereira, Daniela; Pinto, Rita; Almeida, Raquel; Söderberg, Ola; Mandel, Ulla; Clausen, Henrik; Felix, Ana; Lunet, Nuno; David, Leonor
Abstract : The CA125 assay detects circulating MUC16 and is one of the most widely used cancer biomarkers for the follow‐up of ovarian cancer. We previously demonstrated that detection of aberrant cancer‐associated glycoforms of MUC16 as well as MUC1 in circulation could improve the yield of these serum assays. Our aim was to refine ovarian cancer biomarkers by detection of aberrant glycoforms (Tn, STn, and T) of MUC16 and MUC1 in ovarian cancer tissue using Proximity Ligation Assays (PLA). We studied two series of serous ovarian tumours, a pilot series of 66 ovarian tumours (27 cystadenomas, 16 borderline tumours and 23 adenocarcinomas) from Centro Hospitalar S. João, Porto and a validation series of 89 ovarian tumours (17 cystadenomas, 25 borderline tumours and 47 adenocarcinomas) from the Portuguese Institute of Oncology Francisco Gentil, Lisbon. PLA reactions for MUC16/Tn, MUC16/STn, MUC1/Tn and MUC1/STn were negative in benign lesions but often positive in borderline and malignant lesions, in both series. An even better yield was obtained based on positivity for any of the four glyco‐mucin profiles, further increasing sensitivity to 72% and 83% in the two series, respectively, with 100% specificity. The strategy is designated glyco‐mucin profiling and provides strong support for development of PLA‐based serum assays for early diagnosis. Highlights: Development of a glyco‐mucin profile of serous ovarian tumours. Using Proximity Ligation Assays (PLA). Validation using a unique isogenic cell system with knock‐out of COSMC gene. O‐glycosylation of MUC16 and MUC1 identifies malignant/borderline tumours. Glyco‐mucin profiling strategies provide support for development of serum assays.